Beyond the Cover: An In-Depth Analysis of the Practicality of an English Textbook by the Indonesian Government Post Pandemic Covid-19 - Nur Hidayati, Diyah; Kusumawati , Eny (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
For teaching and student learning, textbooks are a vital and widely used resource. The purpose of this study was to assess the unit design in "Bahasa Inggris kelas XI Semester I" to respond the post-pandemic Covid-19. This study was classified as a textbook evaluation. Document analysis and interviews were used to collect data. Miles' and Huberman's model was considered to be used in data analysis through data reduction, data display, and conclusion. The study finds that the textbook addresses only three of the six suggested indicators, lacks appropriate images that can aid students' comprehension, and has no clear grading system or instructions for students, which can lead to confusion and undermine their ability to complete tasks successfully. The study recommends that future textbook writers should consider appropriate visuals to complement the text, use pictures as symbols or icons, and provide explicit instructions to guide students towards achieving learning objectives. The findings of the study can inform future textbook writers, teachers, and curriculum developers to improve the quality of English language education in Indonesian schools. Moreover, the study highlights the need for textbooks to adapt to the new normal of remote learning.